Filozofia sensu jako odpowiedź na kryzys metafizyki. W stronę nowej „filozofii pierwszej" - Śnieżyński, Krzysztof (Poznańskie Studia Teologiczne, 2008)
The desire to validate one’s existence which we call the ultimate and overall sense of life is an inalienable meta-physical experience specific to all humans in their everyday lives. Even if we only speak about the concept of the sense of life, it is always in close relation to a metaphysical experience of validating life as a whole. Such a validation also seeks to express itself in philosophical thinking and that is why the basic question that underpins considerations presented in the paper is as follows: What problem-shape could “first philosophy” assume if it is engaged in the attempt to answer the question that ultimately concerns each of us: the question about the sense of our own existence? Asking about the “problem-shape” of such a philosophy we mean reflection on the philosophy of sense directed to its meta-physical source and not to the formal shape that it could assume. We are not interested in constructing philosophy for philosophy’s sake but our concern is to reflect critically on the “metaphysics-creating experience” which builds and develops the philosophy of the sense of life. The philosophy of sense as a new „first philosophy” will no longer be a philosophy of „being as being” (substance), where that which is most important, „what is first”, pertains either to essence or existence or universal principles of what is labeled as „being”. This new philosophy purports to engage in the most vital problem of life, that is why its task will be, among others, a critical separation of sense and end, thematization of the sense of life in man’s relation to the world, a quest for sense outside a unilateral objectivization (the category of being), reflection on human life in all its manifestations, historical changeability and dramatism, sense as seeking hope greater than “being”, nonidentity of the ultimate sense of life with the ultimate “Safeguardian of Sense” - i.e. God.